Characterisation of 3D trench silicon pixel sensors irradiated at 1⋅1017 1 MeV neqcm-2 - Addison, M.; Bellora, A.; Borgato, F.; Brundu, D.; Cardini, A.; Cossu, G. M.; Dalla Betta, G. F.; La Delfa, L.; Lai, A.; Lampis, A.; Loi, A.; Obertino, M. M.; et al. (Frontiers in Physics, 2024)
The 3D trench silicon pixel sensors developed by the TimeSPOT collaboration have demonstrated exceptional performance, even after exposure to extreme radiation fluences up to 1⋅1017 1 MeV neq/cm2. This study assesses the radiation tolerance of these sensors using minimum ionizing particles during a beam test campaign. The results indicate that while radiation damage reduces charge collection efficiency and overall detection efficiency, these losses can be mitigated to levels comparable to non-irradiated sensors by increasing the reverse bias voltage. Charge multiplication was observed and characterised for the first time in 3D trench sensors, revealing a distinct operating regime post-irradiation achievable at bias voltages close to 300 V. Additionally, the timing performance of irradiated sensors remains comparable to their non-irradiated counterparts, underscoring their resilience to radiation damage. Currently, 3D trench silicon detectors are among the fastest and most radiation-hard pixel sensors available for vertex detectors in high-energy physics colliders. These findings highlight the potential of these sensors for new 4D tracking systems of future experiments at the Future Circular Hadron Collider (FCC-hh), advancing the capabilities of radiation-hard sensor technology.